2012
DOI: 10.4149/neo_2012_021
|View full text |Cite
|
Sign up to set email alerts
|

Lung Adenocarcinoma and Squamous Cell Carcinoma in association with Genetic Polymorphisms of GSTs in Slovak Population

Abstract: Slovak Republic belongs to the countries with high incidence of lung cancer. Gene polymorphisms of the glutathione S-transferases (GSTs) may play a role in individual lung cancer susceptibility. In presented case-control study we investigate the incidence of polymorphism of GSTT1, GSTM1, GSTP1 genes and their combinations as possible predictive factors for identification of individuals with increased risk of formation and development of adenocarcinoma (AC) and squamous cell carcinoma (SCC) of lung in Slovak po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Similarly, inconsistent results regarding an association between the GSTP1 rs1695 A/G polymorphism and LSCC risk have been reported in different races and geographical locations [24, 31, 33, 34, 37, 40, 45, 47, 52, 56, 57, 60, 63]. Here, we failed to detect a positive correlation between GSTP1 rs1695 and LSCC susceptibility, consistent with the prior meta-analysis of Feng in 2013 [66] and Xu in 2014 [67].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, inconsistent results regarding an association between the GSTP1 rs1695 A/G polymorphism and LSCC risk have been reported in different races and geographical locations [24, 31, 33, 34, 37, 40, 45, 47, 52, 56, 57, 60, 63]. Here, we failed to detect a positive correlation between GSTP1 rs1695 and LSCC susceptibility, consistent with the prior meta-analysis of Feng in 2013 [66] and Xu in 2014 [67].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the effect sizes of genetic factors predisposing to human diseases are different in various ethnic populations [66]. Dzian et al [16], Matakova et al [18], and Cajas-Salazar et al [27] suggested that the combined effects of GSTM1 and GSTT1 polymorphisms increased lung cancer risk in Caucasians. Chen et al [22], Liang KC et al [56], Cao YF et al [45], Pan et al [39], Piao et al [40], and Zhang et al [38] suggested that the GSTM1 and GSTT1 polymorphisms in combination were associated with increased risk factors of lung cancer in Asians.…”
Section: Discussionmentioning
confidence: 99%